Haploinsufficiency in non-homologous end joining factor 1 induces ovarian dysfunction in humans and mice. Issue 6 (22nd April 2021) - Li, Guoqing; Yang, Xi; Wang, Lingbo; Pan, Yuncheng; Chen, Siyuan; Shang, Lingyue; Zhang, Yicheng; Wu, Yucheng; Zhou, Zixue; Chen, Qing; Zhang, Xue; Zhang, Ling; et al.
Abstract : Background: Premature ovarian insufficiency (POI) is a common disease in women that leads to a reduced reproductive lifespan. The aetiology of POI is genetically heterogeneous, with certain double-strand break (DSB) repair genes being implicated in POI. Although non-homologous end joining (NHEJ) is an efficient DSB repair pathway, the functional relationship between this pathway and POI remains unknown. Methods and results: We conducted whole-exome sequencing in a Chinese family and identified a rare heterozygous loss-of-function variant in non-homologous end joining factor 1 ( NHEJ1 ): c.532C>T (p.R178*), which co-segregated with POI and irregular menstruation. The amount of NHEJ1 protein in the proband was half of the normal level, indicating a link between NHEJ1 haploinsufficiency and POI. Furthermore, another rare heterozygous NHEJ1 variant c.500A>G (p.Y167C) was identified in one of 100 sporadic POI cases. Both variants were predicted to be deleterious by multiple in silico tools. In vitro assays showed that knock-down of NHEJ1 in human KGN ovarian cells impaired DNA repair capacity. We also generated a knock-in mouse model with a heterozygous Nhej1 variant equivalent to NHEJ1 p.R178* in familial patients. Compared with wild-type mice, heterozygous Nhej1 -mutated female mice required a longer time to first birth, and displayed reduced numbers of primordial and growing follicles. Moreover, these mice exhibited higher sensitivity to DSB-inducing drugs. All these phenotypes are analogous to the progressive loss of ovarian function observed in POI. Conclusions: Our observations in both humans and mice suggest that NHEJ1 haploinsufficiency is associated with non-syndromic POI, providing novel insights into genetic counselling and clinical prevention of POI.